2024
DOI: 10.1002/hsr2.2039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antibiotic resistance pattern for bacteriuria from patients with urinary tract infections

Md. Jubayer Hossain,
Abul Kalam Azad,
Md. Shahadat Bin Shahid
et al.

Abstract: Background and AimsAntibiotic resistance presents a significant global public health challenge, particularly for urinary tract infections (UTIs), and is notably severe in developing countries. Surveillance of the antimicrobial susceptibility patterns of UTI‐causing bacteria is crucial for effective treatment selection. This study aimed to analyze these patterns in bacteria isolated from the urine samples of patients at Mughda Medical College Hospital, Dhaka, Bangladesh.MethodsA retrospective study (January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…30 In addition, a study conducted in Bangladesh revealed that the prevalence of E. coli was 63.6% in women and 36.4% in men. 31 Moreover, this result was in agreement with a study conducted in Peshawar, Pakistan, which reported that the prevalence of E. coli in female patients was 72.7%. 16 The high prevalence of E. coli in females might be linked to the fact that E. coli lives in the periurethral area and the shorter distance between the anal opening, the vaginal cavity and the urethra.…”
supporting
confidence: 91%
“…30 In addition, a study conducted in Bangladesh revealed that the prevalence of E. coli was 63.6% in women and 36.4% in men. 31 Moreover, this result was in agreement with a study conducted in Peshawar, Pakistan, which reported that the prevalence of E. coli in female patients was 72.7%. 16 The high prevalence of E. coli in females might be linked to the fact that E. coli lives in the periurethral area and the shorter distance between the anal opening, the vaginal cavity and the urethra.…”
supporting
confidence: 91%